Problems of small states: {focus on Dominica} - Lazare, Alick ([s.n.] [Roseau]DM, 1991)
Uses the experience of Dominica to illustrate some of the specific difficulties that beset many other small developing countries to a similar or lesser degree. Concludes that small island states are far too vulnerable to survive as independent units in a competitive world unless special conditions are created.